2019
DOI: 10.1109/tbme.2018.2854917
|View full text |Cite
|
Sign up to set email alerts
|

Models for Nociception Stimulation and Memory Effects in Awake and Aware Healthy Individuals

Abstract: A device and methodology for non-invasive for detecting nociception stimulation have been developed. The proposed method and models have been validated on healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…In this particular case, the essential benefit of the ANSPEC-PRO device is that it allows a customizable input signal to the system under observation. In the particular studies case, the ANSPEC-PRO sends a composed multisine with optimal crest factor for optimal extraction of dynamic process information for identification purpose of a process model [13]. MEDSTORM, by contrast, has a single sine input at a single frequency, and the recorded signal back from the skin impedance is not processed as a function of frequency (due to its single point data) but in the time domain, using a moving window averaged amplitude correlated with the pain and awareness in the patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this particular case, the essential benefit of the ANSPEC-PRO device is that it allows a customizable input signal to the system under observation. In the particular studies case, the ANSPEC-PRO sends a composed multisine with optimal crest factor for optimal extraction of dynamic process information for identification purpose of a process model [13]. MEDSTORM, by contrast, has a single sine input at a single frequency, and the recorded signal back from the skin impedance is not processed as a function of frequency (due to its single point data) but in the time domain, using a moving window averaged amplitude correlated with the pain and awareness in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion of sodium/potassium ions changes the typical extracellular concentration, resulting in a negative charged extracellular fluid, so an action potential can be seen as variations of the electrical impedance of the tissue over the nociception pathway. The methodology for the prototype development and measurements are detailed in [13]. The measurement requires three-point electrodes applied on the palmar skin, as illustrated in Figure 2.…”
Section: Monitors Used For Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…When surgical stimulation is present in the overall system, a nociceptor stimulation occurs. A recently developed method, device and model has been presented in [50], based on a physiological model of pain using fractional order tools reviewed in [51]. A simplified model of the nociceptor pathway is described by the following transfer function model:…”
Section: Disturbance and Nociception Stimulationmentioning
confidence: 99%
“…Another feature contributed by the authors is the surgical stimulation nociceptor effect model, as experimentally identified and reported in [50]. The signal is added as a disturbance to the output of the PKPD model of Propofol and Remifentanil.…”
Section: Features Overviewmentioning
confidence: 99%